Efficient formation of vivianite without anaerobic digester: Study in excess activated sludge. Issue 3 (June 2022) - Prot, T.; Pannekoek, W.; Belloni, C.; Dugulan, A.I.; Hendrikx, R.; Korving, L.; van Loosdrecht, M.C.M.
Abstract: It was recently discovered that vivianite (Fe3 (PO4 )2 .8H2 O) could be magnetically extracted from digested activated sludge which opened a new route for phosphorus recovery (Wijdeveld et al. 2022). While its formation in digested sludge is regularly reported, it is not yet studied for fresh, undigested activated sludge. In particular, the extent to which vivianite could form during sludge storage is missing. The current research showed that iron reduction was completed after 2–4 days of anaerobic storage, and the vivianite appeared to form quickly from the pool of reduced iron made available. After sludge thickening at the wastewater treatment plant (30 h retention time), around 11% of the iron was vivianite. With subsequent 1–3 days of anaerobic storage, this fraction increased to 50–55%. After this storage, almost all the vivianite that could potentially form did form. This research concluded that efficient vivianite formation can be achieved without a sludge digester, showing phosphorus recovery potential from undigested sludge via vivianite recovery. Besides, the recovery of vivianite from undigested sludge presents advantages like the reduction of the sludge to dispose of and mitigation of the vivianite scaling formation. Graphical Abstract: ga1 Highlights: More than 80% of the Fe in WAS was reduced after 3 days of anaerobic storage. Vivianite formation in excess activated sludge quickly followed iron reduction. Vivianite bore up to 55% of the Fe and 60% of the P after 2–4 days of storage. Vivianite formation was almost completed after 2–4 days of anaerobic storage. A sludge digester is not necessary for the formation of vivianite in sewage sludge.